A review on neuropsychophysiological correlates of flow - NAH, Fiona Fui-hoon (Institutional Knowledge at Singapore Management University, 2017)
Games are captivating from a human-computer interaction point of view. They can induce an intensely involving and engaging experience termed flow, which refers to the optimal state of experience when one is fully immersed in an activity. This paper provides a review of the neural and psychophysiological correlates of flow as well as some directions for future research.